2023
DOI: 10.3233/wor-220608
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in cardiorespiratory fitness among firefighters based on a fixed 12.0 MET standard and an age-adjusted fitness standard

Abstract: BACKGROUND: Firefighting is a physically demanding profession. Firefighters (FFs) need adequate physical fitness (PF) to perform duty tasks efficiently. While FFs’ work demands are constant throughout their career, there is an expected age-related decline in PF. OBJECTIVE: To describe longitudinal changes in cardiorespiratory fitness (CRF) based on a fixed (12.0 METs) and an age-adjusted standard and compare the prevalence of fit/unfit firefighters (FFs) over eight years. METHODS: 297 Brazilian male firefighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…TT deficiency and CM diseases share common risk factors such as obesity, age, and metabolic syndrome components [ 16 , 21 , 29 , 30 , 31 ]. These risk factors are also related to PF, although the directionality of the relationship is often unclear [ 32 , 33 ]. Although a direct or reverse causality is yet to be clarified, our data support the hypothesis of a complex and negative vicious cycle among these factors, similar to the one proposed by Genchi et al According to this model, the relationship between obesity and hypogonadism potentiates a feedback loop so that each condition further exacerbates the other [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TT deficiency and CM diseases share common risk factors such as obesity, age, and metabolic syndrome components [ 16 , 21 , 29 , 30 , 31 ]. These risk factors are also related to PF, although the directionality of the relationship is often unclear [ 32 , 33 ]. Although a direct or reverse causality is yet to be clarified, our data support the hypothesis of a complex and negative vicious cycle among these factors, similar to the one proposed by Genchi et al According to this model, the relationship between obesity and hypogonadism potentiates a feedback loop so that each condition further exacerbates the other [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although age is a non-modifiable CM risk factor, it is a factor that needs more attention from the Fire Service. A recent study pointed out that fire departments will shortly have more FFs working beyond 60 years due to changes in retirement rules in different countries [ 33 ]. This study showed a significant decrease of CRF (−4.42 mL·(min·kg) −1 ; ≈−1.3 MET) and a simultaneous increase in BMI (+1.25 kg/m 2 ) after 8 years of follow-up of a relatively young cohort of Brazilian military male FFs (36.2 years) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%